Is there a dark side of co-teaching? A study on the social participation of primary school students and their interactions with teachers and classmates. (February 2021) - Spörer, Nadine; Henke, Thorsten; Bosse, Stefanie
Highlights: Interactions between students and teachers were observed at three measurement points. At t1 n  = 193 lessons (t2: n  = 191, t3: n  = 191) were observed. Overall, students interacted more with classmates than with teachers. In co-taught lessons, the probability to interact with teachers increased for students with SEN. The presence of a second teacher had a positive effect on the students' self-perceived acceptance.